2014
DOI: 10.1590/s0100-204x2014000300008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting soil erosion using Rusle and NDVI time series from TM Landsat 5

Abstract: -The objective of this work was to evaluate the seasonal variation of soil cover and rainfall erosivity, and their influences on the revised universal soil loss equation (Rusle), in order to estimate watershed soil losses in a temporal scale. Twenty-two TM Landsat 5 images from 1986 to 2009 were used to estimate soil use and management factor (C factor). A corresponding rainfall erosivity factor (R factor) was considered for each image, and the other factors were obtained using the standard Rusle method. Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
1
16
1
8
Order By: Relevance
“…It is also higher than the findings of earlier researchers in other areas in Ethiopia [27,33,127], and elsewhere in the world [128,129]. On the contrary, the present study results are lower than the findings across the Northwestern Ethiopia highland [130], and other similar studies' findings [131][132][133]. Several previous studies suggested that vulnerability to a higher rate of water-induced soil erosion occurring in eastern Ethiopia's highland is associated with the adverse effects of LULC changes, an unsustainable land management, and less emphasis is given to SWC practices [7,134,135].…”
Section: Discussioncontrasting
confidence: 93%
“…It is also higher than the findings of earlier researchers in other areas in Ethiopia [27,33,127], and elsewhere in the world [128,129]. On the contrary, the present study results are lower than the findings across the Northwestern Ethiopia highland [130], and other similar studies' findings [131][132][133]. Several previous studies suggested that vulnerability to a higher rate of water-induced soil erosion occurring in eastern Ethiopia's highland is associated with the adverse effects of LULC changes, an unsustainable land management, and less emphasis is given to SWC practices [7,134,135].…”
Section: Discussioncontrasting
confidence: 93%
“…Soil physical degradation involves reduction of soil structure, leading to soil compaction, wind and water erosion and soil organic carbon (SOC) mineralization. Although certain classes of soil are more prone to degradation, for instance, Inceptisols and Ultisols (Carvalho et al, 2014), soil mismanagement and land misuse, i.e. indiscriminate plowing and negative SOC budgets may exacerbate soil quality decline (Lal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…So the qualification and quantification of soil erosion, is important as regards, assessing land units because it has effects such as the loss of the nutrients required for crop growth, the accumulation of sediments in river channels, and a reduction in water storage capacity owing to soil loss, thus reducing the natural flow of catchments (Fonseca et al, 2014).…”
Section: Introductionmentioning
confidence: 99%